Digital Knowledge and its Urgencies: reflections on digital immigrants and digital natives - Patricia Margarida Farias Coelho; Marcos Rogério Martins Costa; João Augusto Mattar Neto (Universidade Federal do Rio Grande do Sul, 2018)
The proposals of Don Tapscott (apud Prescott, 2008) and Prensky (2012) are discussed in the educational sphere, evidencing the emergence of a new generation of individuals associated with Information and Communication Technologies (ICTs). This study reflects on the interferences and the potentialities of ICTs, proposing a scale between the knowledge of digital natives and immigrants (Prensky, 2001), from the theoretical-methodological perspective of French semiotics (Fontanille; Zilberberg, 2001). The main educational policies in the Brazilian context in favor of digital education are also discussed, from professional development to the implementation of technologies in school. From theory to pedagogical practice, this is the path outlined in this study.